Antiviral Activity of PLK1-Targeting siRNA Delivered by Lipid Nanoparticles in HBV-Infected Hepatocytes. Issue 3 (April 2020) - Foca, Adrien; Dhillon, Ammen; Lahlali, Thomas; Lucifora, Julie; Salvetti, Anna; Rivoire, Michel; Lee, Amy; Durantel, David
Background: A link between HBV and PLK1 was clearly evidenced in HBV-driven carcinogenesis, and we have also recently shown that PLK1 is a proviral factor in the early phases of HBV infection. Moreover, we have shown that BI-2536, a small molecule PLK1 inhibitor, was very efficient at inhibiting HBV DNA neosynthesis, notably by affecting nucleocapsid assembly as a result of the modulation of HBc phosphorylation. Yet, as small molecule kinase inhibitors often feature poor selectivity, a more specific and safer strategy to target PLK1 would be needed for a potential development against chronic HBV infections. Methods: Here, we analysed using both freshly isolated primary human hepatocytes and differentiated HepaRG, the anti-HBV properties of an LNP-encapsulated PLK1-targeting siRNA. Standard assays were used to monitor the effect of LNP siPLK1, or controls (LNP siHBV and LNP siNon-targeting), on HBV replication and cell viability. Results: A dose as low as 100 ng/ml of LNP-siPLK1 resulted in a >75% decrease in secreted HBV DNA (viral particles), which was comparable to that obtained with LNP siHBV or 10 μM of tenofovir (TFV), without affecting cell viability. Interestingly, and in contrast to that obtained with TFV, a strong inhibition of viral RNA and HBe/HBsAg secretions was also observed under LNP siPLK1 treatment. This correlated with a significant intracellular decrease of vRNA accumulation, which was independent of any change in cccDNA levels, thus suggesting a transcriptional or post-transcriptional modulation. Such an effect was not obtained with a biochemical approach of PLK1 inhibition, suggesting an enzymatic-independent role of PLK1. Conclusions: This study emphasizes that a specific PLK1 inhibition could help in achieving an improved HBsAg loss in CHB patients, likely in combination with other HBsAg-targeting strategies.